Effect Of Organoclay Modification On The Mechanical, Morphology, And Thermal Properties Of Injection Molded Polyamide 6/Polypropylene/Montmorillonite Nanocomposites. - Mohd Ishak, Z.A.; Kusmono, Kusmono; W, S Chow; Takeichi, T; Rochmadi, Rochmadi (2008)

(untitled)
Polyamide 6/polypropylene (PA6/PP = 70/30 parts) blends containing 4 phr (parts per hundred resin) of organophilic montmorillonite (OMMT) were prepared by melt compounding using co-rotating twin-screw extruder followed by injection molding.